Gelatine Backing Affects the Performance of Single-Layer Ballistic-Resistant Materials Against Blast Fragments - Nguyen, Thuy-Tien N.; Meek, George; Breeze, John; Masouros, Spyros D. (Frontiers in Bioengineering and Biotechnology, 2020)
Penetrating trauma by energised fragments is the most common injury from explosive devices, the main threat in the contemporary battlefield. Such devices produce projectiles dependent upon their design, including preformed fragments, casings, glass, or stones; these are subsequently energised to high velocities and cause serious injuries to the body. Current body armour focuses on the essential coverage, which is mainly the thoracic and abdominal area, and can be heavy and cumbersome. In addition, there may be coverage gaps that can benefit from the additional protection provided by one or more layers of lightweight ballistic fabrics. This study assessed the performance of single layers of commercially available ballistic protective fabrics such as Kevlar®, Twaron® and Dyneema®, in both woven and knitted configurations. Experiments were carried out using a custom-built gas-gun system, with a 0.78-g cylindrical steel fragment simulating projectile (FSP) as the impactor, and ballistic gelatine as the backing material. FSP velocity at 50% risk of material perforation, gelatine penetration, and high-risk wounding to soft tissue, as well as the depth of penetration against impact velocity and the normalised energy absorption were used as metrics to rank the performance of the materials tested. Additional tests were performed to investigate the effect of not including a soft-tissue simulant backing material on the performance of the fabrics. The results show that a thin layer of ballistic material may offer meaningful protection against the penetration of this FSP. Additionally, it is essential to ensure a biofidelic boundary condition as the protective efficacy of fabrics was markedly altered by a gelatine backing.